How Can Plants Help Restore Degraded Tropical Soils? - Renaud Massoukou Pamba; Vincent Poirier; Pamphile Nguema Ndoutoumou; Terence Epule Epule (Land, 2023)
In the tropics, anthropogenic activities can lead to water and wind erosion, a loss of biodiversity, and a reduction in sequestered carbon, fertility, and organic matter content in the soils concerned, potentially resulting in their degradation. This study therefore aims to identify the mechanisms used by plant species to restore degraded tropical soils and plant species characteristics that are best suited to achieve this through a critical scoping review of the peer-reviewed literature. Soil restoration leads to the re-establishment of ecosystem services and an increase in soil production potential, the regeneration of biodiversity, the stopping of organic matter losses, and the creation of favorable conditions for carbon sequestration and nitrogen fixation. The choice of appropriate plant species depends on the restoration objectives to be achieved. Five key mechanisms by which plant species contribute to restore degraded tropical soils include: (1) nitrogen fixation, (2) carbon sequestration, (3) organic matter addition, (4) structure stabilization, and (5) erosion control. The main characteristics of plant species and vegetation involved in these mechanisms are (a) the capacity to form symbiotic associations with N-fixing bacteria and mycorrhizae, (b) the production of abundant root biomass releasing litter and exudates, (c) roots having a high length density, branching intensity, and depth distribution, (d) the production of an abundant and easily decomposed above ground litter, (e) the production of a vast canopy, and (f) the presence of different vegetation strata. Targeting these characteristics will contribute to acting on several mechanisms simultaneously, which will increase the chance of success in tropical soil restoration.